Verbal and Nonverbal Languages in Online Thesis Examinations: An Illocutionary Act Study - Hastari Mayrita; Yundi Fitrah; Amirul Mukminin; Sunda Ariana; Marzul Hidayat; Fortunasari Fortunasari (Qubahan Academic Journal)
Research problem is how the use of verbal and nonverbal language in illocutionary speech acts, in communicating on online thesis examinations. Study aimed to describe the types of illocutionary acts, the use of verbal and nonverbal language in online thesis examinations. The method used was qualitative, case study. The collecting data used document review while data analysis utilized content analysis. The research findings showed that, 1) Type of constative illocutionary act namely ascriptive, informative, assertive, responsive, retractive, assertive, confirmative, and disputative; The directive illocutionary acts namely requestees, questions, requirements, prohibitive, permissive, and advisories; Commissive illocutionary acts namely promises; and the illocution acts of acknowledgment. 2) Subsequent findings; Verbal language in constative acts was found verbs to inform, assess, confirm, respond, convey, admit, question, observe, justify, presume with theory, speculate, reject or accept, report, object to, and clarify; directive acts was verbs to instruct, command, direct, require, suggest, encourage, warn, propose, advise, plead/ask, affirm,  authorize, give opportunity, allow, ask and interrogate, and prohibit; commissive acts was verbs to 'make a promise and agree'; and the act of acknowledgment has the verbs to 'greeting', 'introduce oneself', 'thank', 'apologize', and the verb of 'hope'. Further findings, 3) The nonverbal language found were gestures; illustrator, regulator, emblem, or adaptor: facial expressions found based on linguistic terms are syntactic display, speaker semantic display, and listener semantic adaptor. The research findings have implications for reference and literature in linguistic theory, language skills (speaking and listening), and language learning with linguistic communication approach, both offline and online.